Mechanics of biological systems and materials. Proceedings of the 2015 Annual Conference on Experimental and Applied Mechanics /: Proceedings of the 2015 Annual Conference on Experimental and Applied Mechanics. Volume 6 : (2015) - Unknown
No abstract available